A non-inferiority and GLP-compliant study of broflanilide IRS (VECTRON™ T500), a novel meta-diamide insecticide against Anopheles arabiensis - Mbewe, Njelembo J.; Kirby, Matthew J.; Snetselaar, Janneke; Kaaya, Robert D.; Small, Graham; Azizi, Salum; Ezekia, Kisengwa; Manunda, Baltazari; Shirima, Boniface; Mosha, Franklin W.; Rowland, Mark W. (Frontiers in Tropical Diseases, 2023)
Management of insecticide resistance in vector control requires development and evaluation of active ingredients (AIs) with new modes of action. VECTRON™ T500 is a wettable powder formulation used for Indoor Residual Spraying (IRS) containing 50% of broflanilide as an AI. This study evaluated the efficacy of VECTRON™ T500 sprayed on blocks of different substrates (concrete, mud and plywood) against pyrethroid susceptible and resistant Anopheles gambiae sensu stricto (s.s.) strains, and wild An. arabiensis. It also assessed the efficacy of VECTRON™ T500 in experimental huts plastered with mud and concrete against wild free-flying An. arabiensis; and non-inferiority to a World Health Organization listed indoor residual spraying product Actellic® 300CS in terms of mortality in Moshi, Tanzania.Monthly cone bioassays on blocks and in experimental huts (against pyrethroid susceptible and resistant An. gambiae s.s.) were conducted over a 12-month period after spraying of VECTRON™ T500 and Actellic® CS300. Collections of wild free-flying An. arabiensis were also done in the sprayed huts. The main outcome for cone bioassays was mortality while for the wild hut trial collections, it was mortality and blood feeding inhibition. Grouped logistic regressions with random effects were used to analyse all dichotomous outcome variables from wild collections.The results showed residual efficacy of VECTRON™ T500 of at least 80% mortality was longest on concrete, followed by plywood and then mud substrates for all mosquito strains. Furthermore, VECTRON™ T500 significantly increased the likelihood of mortality (OR:> 1.37, P<0.001) in wild collections of An. arabiensis compared to Actellic® 300CS. Blood feeding was not significantly different in the wild collection of An. arabiensis between VECTRON™ T500 and Actellic® 300CS arms.These results show that VECTRON™ T500 is efficacious against pyrethroid-resistant An. gambiae s.s. and non-inferior to Actellic® 300CS. Therefore, it should be an important addition to the current arsenal of insecticides used for insecticide resistance management and vector control.